Treatment and Survival of Patients with Colon Cancer Aged 80 Years and Older: A EURECCA International Comparison. (23rd March 2018) - Vermeer, Nina C.A.; Claassen, Yvette H.M.; Derks, Marloes G.M.; Iversen, Lene H.; van Eycken, Elizabeth; Guren, Marianne G.; Mroczkowski, Pawel; Martling, Anna; Johansson, Robert; Vandendael, Tamara; Wibe, Arne; Moller, Bjorn; et al.
Abstract : Background: Colon cancer in older patients represents a major public health issue. As older patients are hardly included in clinical trials, the optimal treatment of these patients remains unclear. The present international EURECCA comparison explores possible associations between treatment and survival outcomes in elderly colon cancer patients. Subjects, Materials, and Methods: National data from Belgium, Denmark, The Netherlands, Norway, and Sweden were obtained, as well as a multicenter surgery cohort from Germany. Patients aged 80 years and older, diagnosed with colon cancer between 2001 and 2010, were included. The study interval was divided into two periods: 2001–2006 and 2007–2010. The proportion of surgical treatment and chemotherapy within a country and its relation to relative survival were calculated for each time frame. Results: Overall, 50, 761 patients were included. At least 94% of patients with stage II and III colon cancer underwent surgical removal of the tumor. For stage II–IV, the proportion of chemotherapy after surgery was highest in Belgium and lowest in The Netherlands and Norway. For stage III, it varied from 24.8% in Belgium and 3.9% in Norway. For stage III, a better adjusted relative survival between 2007 and 2010 was observed in Sweden (adjusted relative excess risk [RER] 0.64, 95% confidence interval [CI]: 0.54–0.76) and Norway (adjusted RER 0.81, 95% CI: 0.69–0.96) compared with Belgium. Conclusion: There is substantial variation in the rate of treatment and survival between countries for patients with colon cancer aged 80 years or older. Despite higher prescription of adjuvant chemotherapy, poorer survival outcomes were observed in Belgium. No clear linear pattern between the proportion of chemotherapy and better adjusted relative survival was observed. Implications for Practice: With the increasing growth of the older population, clinicians will be treating an increasing number of older patients diagnosed with colon cancer. No clear linear pattern between adjuvant chemotherapy and better adjusted relative survival was observed. Future studies should also include data on surgical quality. Abstract : The aim of this international comparison was to compare treatment strategies and relative survival between countries for older patients with colon cancer, using data from population‐based cancer registries across Europe.